The Role of Ethylene in Plant Adaptations for Phosphate Acquisition in Soils – A Review - Neumann, Günter (Frontiers in Plant Science, 2016)
Although a role of ethylene in the regulation of senescence and plant stress responses in general has a long history, a possible involvement in the regulation of adaptive responses to nutrient deficiencies has been mainly investigated since the last two decades. In the case of plant responses to phosphate (P) starvation, ethylene was identified as a modulator of adaptive responses in root growth and morphology and the molecular base of these adaptations has been elucidated in supplementation studies with ethylene precursors and antagonists, as well as analysis of mutants and transgenic plants with modified ethylene biosynthesis and responsiveness, using mainly Arabidopsis thaliana as a model plant. However, increasing evidence suggests that apart from root growth responses, ethylene may be involved in various additional plant adaptations to P limitation including P mobilisation in the rhizosphere, P uptake and internal P recycling. The ethylene-mediated responses are frequently characterised by high genotypic variability and may partially share common pathways in different nutrient limitations.